Manipulating Kv4.2 identifies a specific component of hippocampal pyramidal neuron A-current that depends upon Kv4.2 expression - Lauver, Aaron (2006)
The somatodendritic A-current, I(SA), in hippocampal CA1 pyramidal neurons regulates the processing of synaptic inputs and the amplitude of back propagating action potentials into the dendritic tree, as well as the action potential firing properties at the soma. In this study, we have used RNA interference and over-expression to show that expression of the Kv4.2 gene specifically regulates the I(SA) component of A-current in these neurons. In dissociated hippocampal pyramidal neuron cultures, or organotypic cultured CA1 pyramidal neurons, the expression level of Kv4.2 is such that the I(SA) channels are maintained in the population at a peak conductance of approximately 950 pS/pF. Suppression of Kv4.2 transcripts in hippocampal pyramidal neurons using an RNA interference vector suppresses I(SA) current by 60% in 2 days, similar to the effect of expressing dominant-negative Kv4 channel constructs. Increasing the expression of Kv4.2 in these neurons increases the level of I(SA) to 170% of the normal set point without altering the biophysical properties. Our results establish a specific role for native Kv4.2 transcripts in forming and maintaining I(SA) current at characteristic levels in hippocampal pyramidal neurons.